2022
DOI: 10.1101/2022.11.17.516971
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IκBα controls dormancy induction in Hematopoietic stem cell development via retinoic acid

Abstract: Recent findings are challenging the classical hematopoietic model in which long-term hematopoietic stem cells (LT-HSC) are the base of the hematopoietic system. Clonal dynamics analysis of the hematopoietic system indicate that LT-HSC are not the main contributors of normal hemapoiesis in physiological conditions and the hematopoietic system is mainly maintained by multipotent progenitors (MPPs, hereafter HPC) and LT-HSCs are mostly in a non-active state. The first HSCs emerge from the aorta-gonad and mesoneph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…While IκBα is commonly known for its role as an inhibitor of the NF-κB signaling pathway (Zhang et al 2017), our laboratory has previously furnished compelling evidence of its alternative role through its interaction with histones and other chromatin components (Aguilera et al 2004; Mulero et al 2013; Marruecos et al 2021). We have demonstrated that chromatin-bound IκBα plays a crucial role in regulating skin and intestinal stem cells (Mulero et al 2013; Marruecos et al 2020), hematopoietic stem cell development (Thambyrajah et al 2022), and it influences the regenerative capacity of these tissues, and in some cases, their susceptibility to neoplastic transformation. Disentangling the chromatin-related function of IκBα from its canonical role as an inhibitor of NF-κB has been challenging, making it difficult to determine its truly biological significance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While IκBα is commonly known for its role as an inhibitor of the NF-κB signaling pathway (Zhang et al 2017), our laboratory has previously furnished compelling evidence of its alternative role through its interaction with histones and other chromatin components (Aguilera et al 2004; Mulero et al 2013; Marruecos et al 2021). We have demonstrated that chromatin-bound IκBα plays a crucial role in regulating skin and intestinal stem cells (Mulero et al 2013; Marruecos et al 2020), hematopoietic stem cell development (Thambyrajah et al 2022), and it influences the regenerative capacity of these tissues, and in some cases, their susceptibility to neoplastic transformation. Disentangling the chromatin-related function of IκBα from its canonical role as an inhibitor of NF-κB has been challenging, making it difficult to determine its truly biological significance.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified an alternative nuclear function of IκBα involving the interaction with histone deacetylases (HDACs), core elements of the Polycomb Repressor Complex 2 (PRC2) and histones (Aguilera et al 2004; 4 Mulero et al 2013;Marruecos et al 2021). This nuclear IκBα function is crucial for tissue stem cell homeostasis and the proper differentiation of epidermal, intestinal and hematopoietic cells (Mulero et al 2013;Marruecos et al 2020Marruecos et al , 2021Thambyrajah et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation